Explaining cyberstalking victimization against college women using a multitheoretical approach: self-control, opportunity, and control balance - Reyns, Bradford W. (Crime & delinquency, 2018)
The foci of the present study are to estimate the extent of cyberstalking victimization, and develop, specify, and test a theoretically based model of cyberstalking victimization among college women. A pursuit- and fear-based measure of victimization was utilized, and three leading theories—self-control, opportunity, and control balance—were tested as explanations of cyberstalking victimization. Key concepts from each theoretical perspective were operationalized using primary survey data from a probability sample of college women (N = 1,987) from two large universities. Results show that approximately 3.4% of female students were victims of cyberstalking during the academic year. Findings from a path model revealed significant direct effects for opportunity and having a control deficit on cyberstalking. The effects of self-control were indirect through these two measures, whereas having a control surplus was not related to victimization risk. Overall, findings support the application of these three theoretical approaches to predicting and explaining cyberstalking victimization.